2009
DOI: 10.1021/ac902101e
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Transmission Mode Desorption Electrospray Ionization: Increasing the Specificity of Ambient Ionization Mass Spectrometric Analyses

Abstract: Fabrication and utilization of mesh materials specifically designed to capture analytes from solution facilitates the direct coupling of affinity capture and ambient ionization mass spectrometry via surface-enhanced transmission mode desorption ionization (TM-DESI). Incorporation of photolabile groups within the linkage between the mesh surface and the covalently modified reactive probe affords facile release of mass tagged analytes directly to mesh surfaces that have been rinsed free of matrix interferences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The results presented here demonstrate that the increased selectivity afforded by analyte capture can be merged with the high throughput capabilities of ambient ionization mass spectrometry via the utilization of mesh substrates specifically designed to both chemoselectively capture target analytes from solution and integrate seamlessly to transmission mode desorption electrospray ionization mass spectrometry (TM-DESI-MS) 3638. While broadly applicable, the present study focuses specifically on sulfhydryl analytes which are prevalent in pharmaceuticals and human metabolism 3941.…”
mentioning
confidence: 99%
“…The results presented here demonstrate that the increased selectivity afforded by analyte capture can be merged with the high throughput capabilities of ambient ionization mass spectrometry via the utilization of mesh substrates specifically designed to both chemoselectively capture target analytes from solution and integrate seamlessly to transmission mode desorption electrospray ionization mass spectrometry (TM-DESI-MS) 3638. While broadly applicable, the present study focuses specifically on sulfhydryl analytes which are prevalent in pharmaceuticals and human metabolism 3941.…”
mentioning
confidence: 99%
“…(Venter, et al, 2006) The effects of the nebulizing gas are clearly discernible is the absence of any overt coulombic effect. The performance and characteristics of DESI were found to be dependent on the choice of the solvent (Tawiah et al, 2010), substrate (Ifa et al, 2008; Kauppila et al, 2006), and geometry (Chipuk et al, 2010; Kertesz & Van Berkel, 2008; Venter & Cooks, 2007). Experiments on solvent composition showed that different chemical information can be obtained by changing the solvent system.…”
Section: Ambient Ionization Imaging Techniquesmentioning
confidence: 99%
“…An important feature of sampling materials for ambient ionization mass spectrometry is their polarity. Hydrophobic materials such as polymethylmethacrylate and polytetrafluoroethylene have been shown to have enhanced signal intensity and stability over less hydrophobic materials used in desorption ionization techniques . Paper coated with a variety of different compounds has also been shown to have enhanced performance as sample support in paper‐spray mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%